PRESERVATION OF CRAFT HERITAGE AND ITS POTENTIAL IN YOUTH ECONOMIC EMPOWERMENT - W. Ariffin, W.N. Jazmina; Shahfiq, Syed; Ibrahim, Asmawi; Mohd Pauzi, Hezzrin; Md Rami, Ahmad Aizuddin (PLANNING MALAYSIA, 2023)
The community's involvement in preserving cultural heritage is very important and greatly impacts it. One of the ways to involve the community in the preservation of cultural heritage, especially in fine arts and crafts, is to combine those efforts with economic benefits for the target group. The strategy will attract the community's interest, especially those looking for a job or wanting to increase their economic resources. Financial problems, job loss, and unemployment are big issues among today's youth. The study focuses on forming a step that can act as a double-edged sword that aims at two objectives; preserve cultural heritage and create new economic resources, especially for the youth. Therefore, this study aims to identify the potential of intangible cultural heritage (fine arts and crafts) in creating new economic resources for youth facing unemployment. This study was carried out using a mixed-methodology approach which is a combination of quantitative and qualitative implemented in Malaysia covering all zones, namely North Zone (Penang), West/Central Zone (Selangor), East Zone (Terengganu) and East Malaysia Zone (Sabah). The questionnaire involved 155 youth groups involved in the traditional craft sector. In-depth interview method with respondents consisting of government bodies such as the National Heritage Department, the Malaysian Handicrafts Development Corporation, and NGOs from other relevant agencies. The results of the study found that intangible cultural heritage (fine arts and crafts) can be preserved by making it a new economic resource among the youth. With the support of the government, help from the aspect of training, and the interest of the youth itself, the craft heritage has the potential to generate income while guaranteeing the sustainability of this cultural heritage. This study is expected to be a backup for the government in designing any cultural heritage preservation program that greatly impacts the community, especially the youth. It becomes a new economic source for them.